Réponses

  • Utilisateur Brainly
2014-04-01T10:25:25+02:00
Simplifications:

B= 13 +6x -3 -3x +4 +x
B= 6x -3x +x  +13 -3 +4
B= 4x + 14

C= 5x +2x +32 -x +1 -5
C= 5x +2x -x  +32 +1 -5
C= 6x + 28

D= a -a +b +a -b +b -a +b -a +b +a -b +a +b +b +b +b
D= a -a +a -a -a +a +a   +b -b +b +b +b -b + b +b +b +b
D= 4a -3a + 8b - 2b
D= a +6b 


Voilà ! J'espère t'avoir aidé(e) ! :)
2014-04-01T11:11:15+02:00

Il faut regrouper les termes puis calculer :

a=a-a+b+a-b+b-a+b-a+b+a-b+a+b+b+b+b

a=(a-a+a-a-a+a+a)+(b-b+b+b+b-b+b+b+b+b)

a= (4a-3a) + (8b-2b)

a= a + 6b

b=13+6x-3-3x+4+x

b= 13 - 3 + 4 + 6x - 3x +x

b= 14 + 4x

c=5x+2x+32-x+1-5

c= 5x + 2x - x + 32 +1 -5

c = 6x + 28